Inklinacje rolników indywidualnych do realizacji inwestycji rzeczowych w gospodarstwach rolnych - Czerwińska-Kayzer, Dorota (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The main goal of this article was to determine the probability of real investments in individual farms. Apart from that, the article is an attempt to make a typology of farms according to the real investments criterion. As results from the investigations, the following factors are decisive to the decision about investments in a farm: the farm area, the production level, the farmer’s age and the assessment of the financial situation of the farm. Investments are (and probably will be) made in large-area farms, with intensive production, managed by young and well educated farmers, who see their future in the farming activity. Apart from that, these farmers use subsidies from the European Union to make considerable investments. On the other hand, older and worse educated farmers, who manage smaller-area farms and have less intensive production, tend to be less likely to make investments in farms.